Knowledge Management Audit for AIU-MRTC's Infrastructure Group - Francisco, Ma. Elizabeth A.; Talisayon, Serafin (Quezon City University of the Philippines Diliman, 2006)
Knowledge plays a strategically important role in ensuring and sustaining the success of an organization. In today's competitive world, mining the tacit knowledge of employees can be considered as one of the competitive strategies of a firm. According to Paul Chin [2], the norm is that every company has what is called isolated "pockets" of knowledge contained in the heads of employees throughout the organization's various departments and workgroups, not realizing that a large portion of the population may benefit from codifying the experiences, expertise and know-how of knowledge workers. Usually, too much time is wasted by the employees in trying to figure out a problem or looking for steps on how to perform certain tasks. Although a knowledge sharing has always taken place informally between certain groups of employees, it becomes a problem when the knowledge worker leaves the organization since they take their expertise with them. In the event that the knowledge worker has transferred his expertise through formal means (i.e. knowledge transfer), it is too much to expect that at least 80 percent of the departing employee's tacit knowledge has been captured and transferred successfully. It is hoped that the knowledge transferred to the remaining employees will continue and sustain the knowledge of life cycle. As David Skyme [12] indicated in the article "The 3Cs of Knowledge Sharing", one of the challenges of knowledge management is that of getting people to share their knowledge. Why should people give up their hard-won knowledge, when it is one of their key sources of personal advantage? In some organizations, sharing is natural. In others the old dictum "knowledge is power" reigns. One of the fundamental steps in implementing a Knowledge Management System in an organization is the conduct of a Knowledge Management Audit. The KM issues presented above are some of the things that this project will try to uncover. In carrying out a Knowledge Management Audit for the Infrastructure Group of American International Underwriters-Manila Regional Technology Center (or AIU-MRTC), we will look at the KM issues faced by the Infrastructure Group such as cultural, organizational and technological issues, which hinder knowledge flow, knowledge sharing, and knowledge growth; the group's knowledge needs and knowledge gaps; and potential risks to its current KM practices, etc. We will also look at some of the recommended strategies and next steps which the Infrastructure Group can pursue to improve its knowledge management practices.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: AIU-MRTC's Infrastructure Group; Knowledge management; Knowledge Management Audit